Clinical Experience of Yan Changhong in the Treatment of Acne with Modified Loquat Qingfei Decoction Combined with Bloodletting and Cupping at Special Acupoints - Zhao, Tenglu; He, Yuxuan; Yan, Changhong (Journal of Contemporary Medical Practice, 2024)
Acne is one of the common and frequent diseases in clinic, Prof. Yan Changhong is a famous traditional Chinese medicine practitioner in Baotou City with rich clinical experience. He believes that the key organs of acne are in the lungs and the disease is in the skin, it is also related to the spleen and the stomach. The main mechanism is that the lungs and the stomach are full of heat, the heat and toxin are embedded in the skin, and the main pathological factors are toxicity, heat, dampness, phlegm, and blood stasis. Prof. Yan Changhong often applies the modified Loquat Qingfei Decoction combined with bloodletting and cupping at special acupoints.